2019
DOI: 10.1016/j.ijfatigue.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of various prior creep-fatigue interaction damages on subsequent tensile and creep properties of 9%Cr steel

Abstract: The degradation of tensile and creep properties is inevitable during high temperature service operation. Hence this work aims to evaluate the effect of prior creep-fatigue interaction damages on remnant tensile and creep properties of 9%Cr steel. Prior creep-fatigue tests interrupted at different lifetime fractions and different tensile hold times are performed at 650 °C. Afterwards, subsequent tensile and creep tests are conducted at the same temperature. Results reveal that high lifetime fraction of prior cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…Besides the loading mode, the exertion of duration period also influenced the creep‐fatigue performance. The effect of prior CFI damages and prior fatigue damage on remaining tensile and creep properties of 9%Cr steel was studied by Zhang et al 30,31 and revealed the prior performance could significantly reduce tensile strength and creep resistance. When studying the performance of alloy 709, Porter et al 32 and Amrita et al 25 also found that creep‐fatigue life was reduced in comparison with low cycle fatigue life at different temperatures, and more life reduction was observed at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the loading mode, the exertion of duration period also influenced the creep‐fatigue performance. The effect of prior CFI damages and prior fatigue damage on remaining tensile and creep properties of 9%Cr steel was studied by Zhang et al 30,31 and revealed the prior performance could significantly reduce tensile strength and creep resistance. When studying the performance of alloy 709, Porter et al 32 and Amrita et al 25 also found that creep‐fatigue life was reduced in comparison with low cycle fatigue life at different temperatures, and more life reduction was observed at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results have revealed that remnant creep properties of P92 steel varied a lot with respect to lifetime fraction, strain amplitude and hold time of prior fatigue loading [13,16,20]. The higher lifetime fraction and strain amplitude the more catastrophic degradation of remnant creep strength was noticed.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed experimental procedures and results have been reported in our previous works [13,16,20], therefore, to avoid a repeated description, only the main experimental procedures and results are presented in the current work. The schematic representation of the experimental procedures is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue behaviors at high temperature are the major concerns for service. It is related to the creep-fatigue, low-cycle fatigue (LCF), and high-cycle fatigue (HCF) at the high temperature [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%